Genome-Wide Identification of TLP Gene Family and Their Roles in Carya cathayensis Sarg in Response to Botryosphaeria dothidea - Li, Peipei; Xu, Yifan; Wang, Ketao; Guo, Wenlei; Gu, Yujie; Lyu, Shiheng; Huang, Jianqin; Lin, Haiping; Huang, Chunying; Xu, Zhen; Li, Yan (Frontiers in Plant Science, 2022)
Hickory (Carya cathayensis) is a critical tree species of the genus Carya from the Juglandaceae family that contains nutrient-rich nuts. Due to large-scale soil degradation, the pests and diseases of hickory are becoming more and more serious. Thaumatin-like proteins (TLPs) are vital proteins involved in the complex defense process of plant pathogens. In this study, 40 CcTLP genes were identified genome-widely and phylogenetically grouped into three subfamilies. The sequence of CcTLPs had a conservative pattern, including eight stable disulfide bonds, REDDD, G-X-[GF]-X-C-X-T-[GA]-D-C-X(1,2)-G-X-(2,3)-C structure. Fifty-seven cis-elements related to stress-responsive, light-responsive, phytohormone-responsive, and plant-responsive were discovered. Under salicylate (SA), methyl jasmonate (MeJA), and ethephon (ETH) treatments, the expressions of CcTLP28, CcTLP29, CcTLP30, CcTLP31, CcTLP32, CcTLP33, CcTLP37, CcTLP38, and CcTLP39 had different patterns. This is an indication that most of TLP genes were upregulated by SA and downregulated by MeJA. Notably, seven TLP genes were significantly upregulated under the Botryosphaeria dothidea inoculation, especially CcTLP31, with an over 20-fold change. Nine genes were shown by subcellular localization analysis to be located at the plasma membrane and cytoplasm. The knowledge of the disease-resistant function of the CcTLP family in hickory is promoted by this results. A foundation reference for the molecular breeding of this plant in the future is provided by our findings.